PENGARUH KANDUNGAN SULFAT TERHADAP KUAT TEKAN BETON - Purba, Parhimpunan (METANA, 2007)
Abstract Compressive strength is one of the important mechanical characteristic that it can indicates the concrete performance. One of the important material in concrete making is water. Water have .function as mixing material and treatment material. Water may not contain substrat that harm of concrete. This research is intended to know the influence of sulphate in the water both of as mixing material or treatment material. From this research indicates that the sulphate ion in the water most influence to concrete pressure strength. Key word : Compressive strength, concrete, sulphate, water cement ratio, treatment